Evaluation of the Implementation of Traffic and Road Transportation Safety Supervision in the Infrastructure Sector - Imam Ozali; Euis Saribanon (Green Publisher Indonesia, 2021)
Supervision is the process of determining performance measures and taking actions that can support the achievement of the expected results in accordance with the performance that has been set. With many problems regarding the public transportation service sector in DKI Jakarta, the evaluation of the implementation of supervision as stated in Government Regulation of the Republic of Indonesia No. 37 of 2017 concerning Traffic and Road Transportation Safety, is ensured to be carried out according to existing regulations. The problem in this research is how the implementation of Traffic Safety and Road Transportation in the Infrastructure Sector with the object of the Transportation Company in Jakarta, to solve the problem the author uses a mix method research that combines quantitative and qualitative methods. The output of this research is to produce a quality research and can provide valuable input to the government as a regulator and public transport companies as operators. The results of the study were to determine the extent to which the effectiveness of the implementation of Traffic Safety and Road Transportation in the Infrastructure Sector with the object of the Transportation Company in Jakarta.